Early enteral feeding and nosocomial sepsis in very low birthweight infants. Issue 4 (21st June 2004) - Flidel-Rimon, O; Friedman, S; Lev, E; Juster-Reicher, A; Amitay, M; Shinwell, E S
Abstract : Background: The interrelations between early enteral feeding, necrotising enterocolitis (NEC), and nosocomial sepsis (NS) remain unclear. Objective: To evaluate the effect of age at the introduction of enteral feeding on the incidence of NS and NEC in very low birthweight (VLBW< 1500 g) infants. Methods: Data were collected on the pattern of enteral feeding and perinatal and neonatal morbidity on all VLBW infants born in one centre during 1995–2001. Enteral feeding was compared between infants with and without NS and/or NEC. Results: The study sample included 385 infants. Of these, 163 (42%) developed NS and 35 (9%) developed NEC. Enteral feeding was started at a significantly earlier mean (SD) age in infants who did not develop nosocomial sepsis (2.8 (2.6) v 4.8 (3.7) days, p  =  0.0001). Enteral feeding was introduced at the same age in babies who did or did not develop NEC (3.1 (2) v 3.7 (3) days, p  =  0.28). Over the study period, the mean annual age at the start of enteral feeding fell consistently, and this correlated with the mean annual incidence of NS ( r 2   =  0.891, p  =  0.007). Multiple logistic regression analysis showed age at start of enteral feeding, respiratory distress syndrome, and birth weight to be the most significant predictors of risk of NS (p  =  0.0005, p  =  0.024, p  =  0.011). Conclusions: Early enteral feeding was associated with a reduced risk of NS but no change in the risk of NEC in VLBW infants. These findings support the use of early enteral feeding in this high risk population, but this needs to be confirmed in a large randomised controlled trial.